Complex interaction between circadian rhythm and diet on bile acid homeostasis in male rats. (26th November 2017) - Eggink, Hannah M.; Oosterman, Johanneke E.; de Goede, Paul; de Vries, Emmely M.; Foppen, Ewout; Koehorst, Martijn; Groen, Albert K.; Boelen, Anita; Romijn, Johannes A.; la Fleur, Susanne E.; Soeters, Maarten R.; Kalsbeek, Andries
ABSTRACT: Desynchronization between the master clock in the brain, which is entrained by (day) light, and peripheral organ clocks, which are mainly entrained by food intake, may have negative effects on energy metabolism. Bile acid metabolism follows a clear day/night rhythm. We investigated whether in rats on a normal chow diet the daily rhythm of plasma bile acids and hepatic expression of bile acid metabolic genes is controlled by the light/dark cycle or the feeding/fasting rhythm. In addition, we investigated the effects of high caloric diets and time-restricted feeding on daily rhythms of plasma bile acids and hepatic genes involved in bile acid synthesis. In experiment 1 male Wistar rats were fed according to three different feeding paradigms: food was available ad libitum for 24 h ( ad lib ) or time-restricted for 10 h during the dark period (dark fed) or 10 h during the light period (light fed). To allow further metabolic phenotyping, we manipulated dietary macronutrient intake by providing rats with a chow diet, a free choice high-fat-high-sugar diet or a free choice high-fat (HF) diet. In experiment 2 rats were fed a normal chow diet, but food was either available in a 6-meals-a-day (6M) scheme or ad lib . During both experiments, we measured plasma bile acid levels and hepatic mRNA expression of genes involved in bile acid metabolism at eight different time points during 24 h. Time-restricted feeding enhanced the daily rhythm in plasma bile acid concentrations. Plasma bile acid concentrations are highest during fasting and dropped during the period of food intake with all diets. An HF-containing diet changed bile acid pool composition, but not the daily rhythmicity of plasma bile acid levels. Daily rhythms of hepatic Cyp7a1 and Cyp8b1 mRNA expression followed the hepatic molecular clock, whereas for Shp expression food intake was leading. Combining an HF diet with feeding in the light/inactive period annulled CYp7a1 and Cyp8b1 gene expression rhythms, whilst keeping that of Shp intact. In conclusion, plasma bile acids and key genes in bile acid biosynthesis are entrained by food intake as well as the hepatic molecular clock. Eating during the inactivity period induced changes in the plasma bile acid pool composition similar to those induced by HF feeding.